The Dragon Prophecy: The Fourth Adventure In The Kingdom Of Fantasy - Geronimo Stilton
Join Geronimo on his fourth trip to the Kingdom of Fantasy! I, Geronimo Stilton, was astonished to find myself in the Kingdom of Fantasy for the fourth time. Sterling, the Princess of the Silver Dragons, needed my help! The last existing dragon egg had been stolen from Sterling. If that egg was destroyed, dragons would become extinct forever! I couldn't let that happen. So my friends and I set out across enchanted lands to find the egg and restore peace to the Kingdom of Fantasy. It was a truly amazing adventure!